Uji Aktivitas Karbon Aktif Tongkol Jagung Terimpregnasi Fe2O3 sebagai Biosorben Limbah Warna Metilen Blue - Fauzan Irfandy; Yuli Ristianingsih; Alit Istiani (Eksergi, 2021)
Methylene blue is one of dying waste that causes harmful effect both enviromental and public health risks. A method to overcome the problem is to adsorb it with the activated carbon. Apart from that, corn cob is potential biomass with can convert to activated carbon. The aim of this research is to syntethic and to modify corn cob activated carbon with iron oxide. It is expected to increase the afinity of methylene blue to the activated carbon surface. The modification is done by wet impregnation and the effectiveness of the impregnated corn cob activated carbon is studied by analyse the persen removal of methylene blue in every interval time. The result show that in the concentration range of Fe load impregnation between 1%-3% which has been used, the corn cob activated carbon with concentration of Fe load 2% has the most optimum ability in methylene blue adsorption with the adsorption capacity 44,9%. Moreover, the effect pH shows that in acidic condition the adsorption of methylen blue is better than in netral condition